Modern Italy's founding fathers The making of a postwar republic - White, Steven F. 1955- (Bloomsbury Academic, 2021)
Modern Italy's Founding Fathers" offers a fresh perspective on the genesis of the Italian republic as viewed through the efforts of its three most influential leaders: Christian Democrat Alcide De Gasperi, Socialist Pietro Nenni and Communist Palmiro Togliatti. De Gasperi, the central figure of the study, served as the Republic's inaugural prime minister from 1945 to 1953. In concise, accessible prose, this work demonstrates how De Gasperi and his fellow statesmen's shared experience of Fascist oppression, belief in popular sovereignty, and ability to compromise despite deep ideological differences, enabled the creation of Italy's post-war republic. This collective biography is the first work of its kind in English to examine the genesis of the Italian Republic, commencing with the overthrow of Mussolini in 1943 and concluding with De Gasperi's death in 1954. The study considers the nature of the three mass political parties that emerged at this time as sources of both strength and weakness for the nascent post-war state. Drawing on the personal papers, speeches and writings of the three protagonists, on governmental and party archives, and on significant new Italian secondary scholarship, Steven White demonstrates how these leaders forged political practices and customs which continue to define Italian parliamentary life to the present day. Examining the interplay of personalities, leadership styles, ideas and political context, the work is a vital text for any student of modern Italy and, more broadly, of Cold War Europe
Keywords: Togliatti, Palmiro -- 1893-1964; De Gasperi, Alcide -- 1881-1954; Nenni, Pietro -- 1891-1980; Geschichte 1946-1954; Politik; Italien; Statesmen / Italy / Biography; De Gasperi, Alcide / 1881-1954; Nenni, Pietro / 1891-1980; Togliatti, Palmiro / 1893-1964; Italy / Politics and government / 1945-1976; Partito della democrazia cristiana / Biography; Partito socialista italiano / Biography; Partito comunista italiano / Biography; Cold War; Fascism / Italy / History / 20th century; Partito comunista italiano; Partito della democrazia cristiana; Partito socialista italiano; Fascism; Politics and government; Statesmen; Italy; 1900-1999; Biographies; History; Biografie